2008
DOI: 10.1021/jf073513z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Volatile Compounds Responsible for Prune Aroma in Prematurely Aged Red Wines

Abstract: The premature aging of red Vitis vinifera L. wines is mainly associated with the formation of an intense off-flavor reminiscent of prunes. The compounds responsible for this deterioration in red wine flavor have not previously been identified. Sensory descriptive analysis associated with a gas chromatography-olfactometry (GC-O) technique was first performed to find characteristic odoriferous zones of 15 aged red wines with or without a marked prune aroma. Afterward, high-pressure liquid chromatography, gas chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 33 publications
4
86
0
1
Order By: Relevance
“…In all cases, the oxygen treatment produced an increase of the plum/currant attributes (Fig. 4), closely related to ß-damascenone and c-nonalactone concentrations, according to Pons, Lavigne, Eric, Darriet, and Dubourdieu (2008). A significant decrease in the green attribute was shown in the micro-oxygenated red wines, in spite of the lack of significant differences in C 6 alcohols, responsible for the herbaceous character, previously mentioned (López et al, 2003).…”
Section: Descriptive Sensorial Analysismentioning
confidence: 76%
“…In all cases, the oxygen treatment produced an increase of the plum/currant attributes (Fig. 4), closely related to ß-damascenone and c-nonalactone concentrations, according to Pons, Lavigne, Eric, Darriet, and Dubourdieu (2008). A significant decrease in the green attribute was shown in the micro-oxygenated red wines, in spite of the lack of significant differences in C 6 alcohols, responsible for the herbaceous character, previously mentioned (López et al, 2003).…”
Section: Descriptive Sensorial Analysismentioning
confidence: 76%
“…One recent study suggests that, although no single γ-lactone was found at concentrations above its odor threshold, the lactones in combination may contribute to the aroma of wine through synergistic effects (Cooke et al 2009). In contrast, a separate study correlated γ-nonalactone levels with prune-like aromas in aged red wine (Pons et al 2008), and numerous studies have correlated γ-and δ-lactones with the aroma of botrytized wines from Sauternes (Bailly et al 2009), Barsac, Loupiac (Sarrazin et al 2007a), Campania (sweet Fiano wines) (Genovese et al 2007), and Hungary (Tokaji Aszú) (Miklósy and Kerényi 2004). As less is known about the origins of fatty acid derivatives compared to other grape-derived volatile compounds, further research is warranted to better understand their formation and contribution to wine aroma.…”
Section: Fatty Acid Derivativesmentioning
confidence: 88%
“…It is worth to mention that the plum/ currant aroma was only appreciated in micro-oxygenated red wines. According to Pons, Lavigne, Eric, Darriet, and Dubourdieu (2008), this fact could be closely related to b-damascenone and g-nonalactone concentration, by comparison with plum and dry fruits extracts by Gas Cromatography-Olfatometry.…”
Section: Micro-oxygenation Effect On Sensorial Propertiesmentioning
confidence: 96%